Efikasi Kendiri Kaunseling dan Kecekapan Kaunseling Pelbagai Budaya dalam kalangan Guru Bimbingan dan Kaunseling Sekolah Menengah di Malaysia - Aida Nubaillah Noor; Salleh Amat; Abu Yazid Abu Bakar (Universitas Sebelas Maret, 2018)
The purpose of this study was to examine the level of counseling self-efficacy and level of competency for multicultural counseling among counselors in secondary school in Malaysia. It aims to review the level of counseling self-efficacy and level of competency in multicultural counseling based on gender and experience among secondary school counselors. A total number of 140 respondents (secondary school counselors) have been involved in this research. Result shows that the respondents possess high level of counseling self-efficacy and multicultural counseling competency; and both differ based on gender and length of working experience as secondary school counselors. Moreover, the study exhibits a significant correlation between counseling self-efficacy and multicultural counseling competency. Suggestions and implications from this study were also discussed in this article.